Age determination of ODP sites 169-1033 and 169-1034 - Blais-Stevens, A; Clague, John J; Mathewes, Rolf W; Hebda, R J; Bornhold, Brian D (Supplement to: Blais-Stevens, A et al. (2003): Record of large, Late Pleistocene outburst floods preserved in Saanich Inlet sediments, Vancouver Island, Canada. Quaternary Science Reviews, 22(21-22), 2327-2334, https://doi.org/10.1016/S0277-3791(03)00212-9, 2003)
Two anomalous, gray, silty clay beds are present in ODP cores collected from Saanich Inlet, Vancouver Island, British Columbia, Canada. The beds, which date to about 10,500 14C yr BP (11,000 calendar years BP), contain Tertiary pollen derived from sedimentary rocks found only in the Fraser Lowland, on the mainland of British Columbia and Washington just east of the Strait of Georgia. Abundant illite-muscovite in the sediments supports a Fraser Lowland provenance. The clay beds are probably distal deposits of huge floods that swept through the Fraser Lowland at the end of the Pleistocene. Muddy overflow plumes from these floods crossed the Strait of Georgia and entered Saanich Inlet, where the sediment settled from suspension and blanketed diatom-rich mud on the fiord floor. The likely source of the floods is Late Pleistocene, ice-dammed lakes in the Fraser and Thompson valleys, which are known to have drained at about the time the floods occurred.